GROWTH RATE OF BARRAMUNDI (LATES CALCARIFER) WITH FEED ADDED MANGOSTEEN PEEL (GARCINIA MANGOSTANA) FLOUR AS A GROWTH SUPPLEMENT - Tri Yusufi Mardiana; Linayati Linayati; Diyah Ayu Rosediana; Muhammad Zulkham Yahya (Universitas Mataram, 2024)
Mangosteen peel has the potential to be a growth supplement for barramundi, which has an ever-increasing consumption rate. The aim of this research is to provide literature on the use of mangosteen peel in influencing the growth of white snapper fish and to find the optimal dose that can be used to add to white snapper fish feed. Using a 15 L jar rearing medium with white snapper fish (± 6 cm) and a method using quantitative research RAL 4 treatments adding mangosteen peel to the white snapper fish feed with 3 repeaters. The doses determined in this study were: A (0g/kg feed); B (2g/kg feed); C (4g/kg feed); D (6g/kg feed). And the results obtained by the highest treatment which was able to provide the best growth was D (6g/kg feed) with an average growth of 7.35 with a daily rate reaching 2.52% with all treatments with no deaths and water quality that supported white sea bass with good, namely salinity 31 – 32 ppt, DO 7.3 – 7.9 mg/l, temperature 27 – 28 °C, and pH reaching 7.7 – 8.1.